Estimation of Oxidative Stress and Inflammatory Markers Among Chronic Kidney Disease Patients in Libya - Zainab Hussein EL Mabrouk; Marwa Emaar Al-joki; Nacereddine Toumi (African Journal of Advanced Pure and Applied Sciences, 2026)
The present work is designed to assess the impact of inflammatory and OS biomarkers on the development of CKD. This study included 30 control subjects and 70 CKD patients at stages 2-5, aged 20 to 75 years. Blood specimens were drawn from healthy individuals and patients to estimate kidney parameters, biomarkers of OS (ROS and TAC), and inflammation (IL-1β and CRP). An independent t-test was used for two-group comparisons, ANOVA for multiple comparisons, and Pearson's correlation coefficient for variable relationships. The study revealed progressive renal impairment, with a highly significant decrease (P = 0.000) in estimated Glomerular filtration rate (eGFR) across CKD stages. Conversely, serum levels of creatinine and urea were found to be markedly elevated (P = 0.000) in advanced stages compared to early stages and healthy subjects. Additionally, levels of Interleukin 1β (IL-1β) were considerably higher in the advanced stages compared to the early stage and healthy controls. Moreover, the reactive oxygen species (ROS) level was raised considerably (P = 0.03) in advanced stages compared to earlier stages; meanwhile, total antioxidant capacity (TAC) levels were lower in CKD patients and continued to decrease significantly (P = 0.000) in more advanced stages of the disease. Furthermore, ROS levels demonstrated a strong inverse association with eGFR, while showing a strong positive connection with creatinine and urea. In contrast, TAC exhibited a strong positive association with eGFR and negatively correlated with creatinine, urea, and uric acid. Additionally, CRP and IL1β levels were inversely related to eGFR and positively linked with creatinine and urea. Notably, ROS levels revealed a considerable positive association with both CRP and IL1β, while TAC displayed a significant negative correlation with these markers. Our findings demonstrated that inflammatory and OS biomarkers significantly increased in serum during the early stages of CKD. These results underscore their potential for facilitating early detection and improving strategies for prevention and diagnosis.